MULTIDIMENSIONAL SOLITONS WITH SPHERICAL COMPACTIFICATION - Chopovsky, A. V.; Eingorn, M. V.; Zhuk, A. I. (Одеські астрономічні публікації, 2012)
Multidimensional static spherically symmetric (with respect to the external 3-dimensional space) vacuum solutions of the Einstein equation were well-known and prevalent in literature for a long time. These solutions are called solitons. Among them, there is a class of particular solutions, called latent solitons, which are indistinguishable from General Relativity concerning the gravitational tests. Black strings and black branes belong to this class. We construct an exact soliton solution, when the internal space represents a sphere of some finite radius.